Two-Dimensional Structure of Flow Channels and Associated Upward Field-Aligned Currents: Model and Observations - Lyons, Larry. R.; Nishimura, Yukitoshi; Wang, Chih-Ping; Liu, Jiang; Bristow, William. A. (Frontiers in Astronomy and Space Sciences, 2021)
Flow bursts are a major component of transport within the plasma sheet and auroral oval (where they are referred to as flow channels), and lead to a variety of geomagnetic disturbances as they approach the inner plasma sheet (equatorward portion of the auroral oval). However, their two-dimensional structure as they approach the inner plasma sheet has received only limited attention. We have examined this structure using both the Rice Convection Model (RCM) and ground-based radar and ASI observations. As a result of the energy dependent magnetic drift, the low entropy plasma of a flow burst spreads azimuthally within the inner plasma sheet yielding specific predictions of subauroral polarization stream (SAPS) and dawnside auroral polarization stream (DAPS) enhancements that are related to the field-aligned currents associated with the flow channel. Flow channels approximately centered between the dawn and dusk large-scale convection cells are predicted to give significant enhancements of both SAPS and DAPS, whereas flow channel further toward the dusk (dawn) convection cell show a far more significant enhancement of SAPS (DAPS) than for DAPS (SAPS). We present observations for cases having good coverage of flow channels as they approach the equatorward portion of the auroral oval and find very good qualitative agreement with the above RCM predictions, including the predicted differences with respect to flow burst location. Despite there being an infinite variety of flow channels’ plasma parameters and of background plasma sheet and auroral oval conditions, the observations show the general trends predicted by the RCM simulations with the idealized parameters. This supports that RCM predictions of the azimuthal spread of a low-entropy plasma sheet plasma and its associated FAC and flow responses give a realistic physical description of the structure of plasma sheet flow bursts (auroral oval flow channels) as they reach the inner plasma sheet (near the equatorward edge of the auroral oval).